Análisis del Grado de Accesibilidad en el Restaurante Donde Fercho ubicado en el cantón Babahoyo - Rodriguez Vega, Ilimbor Selena (2022)
Accessibility in tourist spaces is essential for citizens who want to carry out leisure and recreation activities; In addition, these sites must have universal design standards without impeding free access to establishments, which allows tourists with disabilities to move without obstacles. Tourism for all is considered from a perspective of equal access to services provided by a public or private tourism sector without discrimination. The objective of the research is to analyze the degree of accessibility in the Donde Fercho restaurant located in the city of Babahoyo, to collect part of the information, a file on accessibility was used in the establishment, managing to identify deficiencies in the infrastructure that are essential to provide comfortable and adequate attention to tourists with disabilities.